Beyond experiments: Embedding outcomes in climate governance - Sengers, Frans; Turnheim, Bruno; Berkhout, Frans (Environment and planning. C, Politics and space, 2021)
Concerted action on climate change will require a continuing stream of social and technical innovations whose development and transmission will be influenced by public policies. New ways of doing things frequently emerge in innovative small-scale initiatives – ‘experiments’ – across sectors of economic and social life. These experiments are actionable expressions of novel governance and socio-technical arrangements. Mobilising and generalising the outputs of these experiments could lead to deep reductions in greenhouse gas emissions over the long-term. It is often assumed that the groundswell of socio-technical and governance experiments will ‘scale-up’ to systemic change. But the mechanisms for these wider, transformative impacts of experiments have not been fully conceptualised and explained. This paper proposes a conceptual framework for the mobilisation, generalisation and embedding of the outputs and outcomes of climate governance experiments. We describe and illustrate four ‘embedding mechanisms’ – (1) replication-proliferation; (2) expansion-consolidation; (3) challenging-reframing; and (4) circulation-anchoring – for entwined governance and socio-technical experiments. Through these mechanisms knowledge, capabilities, norms and networks developed by experiments become mobile and generic, and come to be embedded in reconfigured socio-technical and governance systems.